Globalized nostalgia : tourism, heritage, and the politics of place - Ceisel, Christina M. (2018)
The library and Archive of Galicia : memory, heritage, and history – Gaiás Center Museum : cultural performances – Center for creative enterprising of Galicia : transnational commodity culture – Centre for cultural innovation : cultural policymaking